The role of long non-coding RNAs in cardiovascular diseases: A comprehensive review - Xuena Xie; Meiwen Huang; Shudong Ma; Qiqi Xin; Yuying Wang; Lantian Hu; Han Zhao; Pengqi Li; Mei Liu; Rong Yuan; Yu Miao; Yizhun Zhu; et al. (Non-coding RNA Research)
Cardiovascular diseases (CVDs) are the leading cause of morbidity and mortality worldwide, posing significant challenges to healthcare systems. Despite advances in medical interventions, the molecular mechanisms underlying CVDs are not yet fully understood. For decades, protein-coding genes have been the focus of CVD research. However, recent advances in genomics have highlighted the importance of long non-coding RNAs (lncRNAs) in cardiovascular health and disease. Changes in lncRNA expression specific to tissues may result from various internal or external factors, leading to tissue damage, organ dysfunction, and disease. In this review, we provide a comprehensive discussion of the regulatory mechanisms underlying lncRNAs and their roles in the pathogenesis and progression of CVDs, such as coronary heart disease, atherosclerosis, heart failure, arrhythmias, cardiomyopathies, and diabetic cardiomyopathy, to explore their potential as therapeutic targets and diagnostic biomarkers.